Adatok a polgári jogintézmények kialakulásához: a szociális gondoskodás tradicionális és modern formái a bonyhádi zsidó közösségben - Nagy, Teodóra Janka (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2018)
The study wishes to contribute to the examination of the evolution of civil legal institutions mainly by reviewing the traditional and modern forms of social care developed in the Jewish community of Bonyhád. Based on historical and archival sources it presents those forms of social caregiving from the 18th century until the World War I that also became incorporated into modern law evolving after the Austro-Hungarian Reconciliation. Based on a local practice, the study wishes to draw attention to how the Chevra Kadisa, the earliest dominant scene of caring for the poor and vulnerable in the Jewish religious communities became the predecessor of major legal institutions (societies, associations) of the civil society developed in the modernisation process of the 19-20th centuries.